Nishamalaki Drug- An Ayurvedic Antioxidant Regimen for Periodontal Diseases and Diabetes Mellitus? (Medical Forum Monthly, 2024)
Numerous epidemiological studies have suggested a link between diabetes and periodontitis, both of which are widespread chronic disorders in the world. It seems that diabetes increases the risk of periodontal disease, although treating periodontitis can also help improve glycemic control. Recently, research has focused on the significance of oxidative stress-inflammatory pathways in the etiology of diabetes and periodontitis. The use of antioxidants in the treatment of periodontal disease has gained importance. Research has indicated that addressing oxidative stress and hyperglycemia concurrently may yield better results than treating hyperglycemia exclusively with intensive care. Nishamalaki, an ayurvedic drug, has both antiglycemic and antioxidant property. This review investigated Nishamalaki’s potential benefits as an antioxidant for treating both periodontal diseases and diabetes.